Dynamic hydrologic and biogeochemical processes drive microbially enhanced iron and sulfur cycling within the intertidal mixing zone of a beach aquifer. (3rd January 2015) - McAllister, Sean M.; Barnett, Joshua M.; Heiss, James W.; Findlay, Alyssa J.; MacDonald, Daniel J.; Dow, Charles L.; Luther, George W.; Michael, Holly A.; Chan, Clara S.
Abstract Intertidal aquifers host a reactive zone comprised of Fe mineral‐coated sands where fresh and saline groundwaters mix. This zone may significantly influence the export of C, N, P, Fe, and other metals in submarine groundwater discharge (SGD). Toward determining the roles of microbes in Fe and S mineralization, and the interplay of microbiology with geochemistry and physical hydrology, we conducted a biogeochemical study of pore waters at Cape Shores, Delaware. Here, fresh groundwater provides Fe(II), which precipitates as FeIIIOOH predominantly through microbial Fe(II) oxidation. Candidate division OP3 was the dominant microbial group associated with Fe(II)‐ and Fe(III)‐rich regions of the aquifer, suggesting that this uncharacterized phylum may be involved in Fe(II) oxidation. Saline water brings O2, sulfate, and organic C into the intertidal mixing zone. Microbial reduction of sulfate produces sulfide that is transported to the Fe‐mineralized zone leading to the transformation of FeOOH to Fe(II) sulfides. Microbial populations are structured by the availability of chemical species supplied along groundwater flow paths. Seasonal changes in the relative supply of fresh and saline groundwater affect solute fluxes, and therefore, microbial controls on the location and composition of the Fe‐mineralized zone. Ultimately, the composition, extent, and dynamics of the Fe‐mineralized zone will affect the sequestration, affinity, and residence time of solutes bound for export to coastal oceans through SGD.